Skrining Kehamilan Sebagai Upaya Peningkatan Kesehatan Ibu Hamil Di Puskesmas Labuhan Rasoki Kecamatan Padangsidimpuan Tenggara Kota Padangsidimpuan 2021 - Irwan Batubara; Sri Juwarni; Ramlan (Jurnal Rumpun Ilmu Kesehatan, 2023)
The aim of this study was to analyze the results of Hb screening of pregnant women in the third trimester and birth weight. Cross sectional observational research. Population of third trimester pregnant women in the Labuhan Rasoki Health Center area, Southeast Padangsidimpuan District, Padangsidimpuan City. The total sample population was 30 respondents. Data were collected for Hb examination using the Easy Touch GHb tool and weighing newborns. Pearson correlation test data analysis. Results: Relationship between age and birth weight. Pearson correlation coefficient value (r) -0.464, significance level (p) 0.007, significant between age and birth weight of the baby. Parity with an r value of -0.300, significance level (p) 0.007, is not significant between parity and birth weight. The r value of pregnancy spacing is -0.234. significance level (p) 0.198, there is a significant relationship between pregnancy distance and birth weight. LILA r value is -0.030, significance level (p) 0.869, there is no significant relationship between LILA measurements and birth weight of the baby. Hemoglobin, r value 0.751, significance level (p) 0.058. There is a significant relationship between third trimester Hb levels and baby birth weight.elationship between external factors which are significantly related to birth weight, age, gestational interval and the Hb level of pregnant women. Arm circumference and parity were not related to birth weight. Pregnant women's Hb is checked every trimester, the data supports care planning.